2023
DOI: 10.3390/v15010248
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response Profile of COVID-19 Reveals Severity and Variant-Specific Epitopes: Lessons from SARS-CoV-2 Peptide Microarray

Abstract: The amaranthine scale of the COVID-19 pandemic and unpredictable disease severity is of grave concern. Serological diagnostic aids are an excellent choice for clinicians for rapid and easy prognosis of the disease. To this end, we studied the humoral immune response to SARS-CoV-2 infection to map immunogenic regions in the SARS-CoV-2 proteome at amino acid resolution using a high-density SARS-CoV-2 proteome peptide microarray. The microarray has 4932 overlapping peptides printed in duplicates spanning the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Similarly, other works analyzing B-cell epitopes observed that RBM sequences (NGVEGFNCYFP) are less serologically reactive than other S1 and S2 regions [REF-A novel precision-serology assay for SARS-CoV-2 infection based on linear B-cell epitopes of Spike protein]. Analogously to our study, a peptide array revealed that highly immunogenic regions belong to regions outside the RBD [40].…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, other works analyzing B-cell epitopes observed that RBM sequences (NGVEGFNCYFP) are less serologically reactive than other S1 and S2 regions [REF-A novel precision-serology assay for SARS-CoV-2 infection based on linear B-cell epitopes of Spike protein]. Analogously to our study, a peptide array revealed that highly immunogenic regions belong to regions outside the RBD [40].…”
Section: Discussionsupporting
confidence: 85%
“…While some prior studies have identified IgA epitopes of the spike protein from SARS-CoV-2 [ 23 , 29 , 31 ], this is the first study to provide a comprehensive list of the IgA epitome. Out of the total epitopes identified, most (32) exhibited cross-reactivity with proteins from DENV and other organisms, including coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Several other investigators have also examined various aspects of the IgA immune response to the S protein in the context of COVID-19. They have utilized various techniques, such as studying fragments of peptides with different sizes [ 29 ], exploring antibody affinity maturation in relation to clinical outcomes in hospitalized COVID-19 patients [ 30 ], employing microarray analysis of peptides to investigate the disease severity over time in a small cohort of patients [ 23 ], and using a microarray of peptides technology to analyze the humoral response profile to COVID-19 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could not only contribute to the optimization of diagnostic and prognostic methods, but also for breaking ground for developing new vaccine strategies. To this end, peptide microarray-based technologies are valuable tools to study host-pathogen interactions at biomolecular level due to their potential for epitope detection at the amino acid resolution ( Acharjee et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%